Electron Microscopic Radioautographic Study on Protein Synthesis in Mitochondria of Binucleate Hepatocytes of Aging Mice - Tetsuji Nagata (The Scientific World Journal)
In order to study the aging changes of intramitochondrial protein synthesis in mouse hepatocytes, 10 groups of aging mice, each consisting of three individuals, total 30, from fetal day 19 to postnatal year 2, were injected with 3H-leucine, a protein precursor, sacrificed 1 h later, and the liver tissues processed for electron microscopic radioautography. On electron microscopic radioautograms obtained from each animal, the numbers of mitochondria, the numbers of labeled mitochondria, and the mitochondrial labeling index labeled with 3H-leucine that showed protein synthesis in each hepatocyte, both mononucleate and binucleate cells, were counted and the averages in respective aging groups were compared. From the results, it was demonstrated that the numbers of mitochondria, the numbers of labeled mitochondria, and the labeling indices of intramitochondrial protein syntheses in both mononucleate and binucleate hepatocytes of mice at various ages increased due to development of animals. The numbers of mitochondria, the numbers of labeled mitochondria, and the labeling indices of intramitochondrial protein synthesis in binucleate hepatocytes were more than those of mononucleate hepatocytes at the same aging stages.